EXPLORING SUITNANOMUSIC PROJECT: AN INTERDISCIPLINARY PERSPECTIVE ON “RATINHOS” FAIENCE PLATES - Galacho, Cristina (2024)
In this communication we present case studies of two groups of ceramic artifacts with musical iconography studied in the frame of the on-going exploratory project Suit- NanoMusic (IN2PAST). Combining knowledge derived from different areas, such as Chemistry, Conservation Science, Musical Iconography and Humanities and Social Sciences, the project triggers an interdisciplinary discussion on the preservation of tangible musical heritage. The studied artefacts represent two groups of the wider collection of faience plates, the “Ratinho” and the Viúva Alfredo de Oliveira (V.A.O.) pottery faience, a production inspired by the ‘Ratinho’ faience. They had been produced in Coimbra region in Central Portugal at different time frames and belong to the Museu Nacional da Música (Portugal). To further understand the chronology of production the technology of the faience plates the chemical composition of the glaze and colouring elements were analysed by means of handheld x-ray fluorescence, and the colourants were identified combining the information acquired by hyperspectral imaging and colorimetry. The colours in both types of plates present similarities, nevertheless, the analysis suggests that there was some innovation regarding the colour palette with the introduction of new materials. Regarding the glaze composition, the presence of zinc in the V.A.O. glaze is the only differentiation detected among the two productions. The Musical Iconographic and Organological studies reveal distinctively characteristic within the decorative repertoire of “Ratinho” plates. Musical instruments play a central role in the iconographic representationin both kinds of productions, where a female musician playing a cittern and a child playing a transverse flute have been depicted. Studying these ceramic plates reveals key insights into their production techniques and the historical, artistic,and cultural dimensions of musical iconography, highlighting the depiction of music and musicians across various eras and contexts, specifically of rural workers which have few coeval written sources exist.